LIFE CYCLE COSTING MODEL BASED ON TARGET COSTING AND ACTIVITY-BASED COSTING METHOD AND A MODEL PROPOSAL - Pazarceviren, Selim Yuksel; Dede, Bayram (European Scientific Journal, ESJ, 2015)
Excessive levels of competition with globalization has forced businesses to differentiate into products and prices. Differentiation in price is only possible with lowest price. Businesses can create differetiation in products by increasing quality of the products and after sales services. To provide these, businesses have to know exact cost of the products and services and they need to design their products and services based on their costs. At this point, conventional cost systems become insuffi-cient and businesses need strategic cost management systems. One of these strategic cost manage-ment tools is the target costing method. Target costing method focuses on design stage of the product and aims to control and reduce the costs before they emerge. Conventional cost systems become insufficient in providing accurate data to target costing. At this point, activity based costing method provides more accurate data to target costing especially in indirect costs of products. After sales services which create differentiation in products have some costs and these costs need to be considered as costs of the products. In this study, a model is proposed for target life cycle costing based on activity based costing. In this model, all costs from design stage to after sales support in product life cycle are considered as product costs and target cost is calculated using activity based costing method. Finally, the model is explained using an example.